Analytical model for macromolecular partitioning during yeast cell division - Kinkhabwala, Ali; Khmelinskii, Anton; Knop, Michael (BMC Biophysics, 2014)
Asymmetric cell division, whereby a parent cell generates two sibling cells with unequal content and thereby distinct fates, is central to cell differentiation, organism development and ageing. Unequal partitioning of the macromolecular content of the parent cell which includes proteins, DNA, RNA, large proteinaceous assemblies and organelles can be achieved by both passive (e.g. diffusion, localized retention sites) and active (e.g. motor-driven transport) processes operating in the presence of external polarity cues, internal asymmetries, spontaneous symmetry breaking, or stochastic effects. However, the quantitative contribution of different processes to the partitioning of macromolecular content is difficult to evaluate.
Gesehen am 09.08.2017